THE INFLUENCE OF PERSONALITY, LIFESTYLE, MONEY ATTITUDE ON CUSTOMER PURCHASE DECISION (CASE STUDY: MANADO GRAND PALACE CONVENTION HALL) - Kowel, Claudia Angelita (Sam Ratulangi University, 2015)
ABSTRACT Weddings have forever been a significant and important celebration for many people around the world. In this research, the object is Manado Grand Palace Convention Hall (MGP). The variables observed are personality, lifestyle, and money attitude. This research aims to analyze the influence of personality, lifestyle and money attitude on customer purchase decision of Manado Grand Palace Convention Hall partially and simultaneously. This research used Multiple Regression Analysis to analyze the data. 100 customers of MGP were surveyed as respondents. The result of this research is there is a positive significant influence of personality, lifestyle, and money attitude to customer purchase decision partially and simultaneously. Most of the respondents use MGP as a wedding place only views of the use it for meeting, gathering or anniversary celebration. Therefore, as the recommendation is to keep the quality of products to engage in the fields of services. Â Keywords: personality, lifestyle, money attitude, customer purchase decision.